2021
DOI: 10.1002/pits.22633
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal trajectories of teacher burnout and vigour across the scholar year: The predictive role of emotional intelligence

Abstract: This study aimed to explore the longitudinal trajectories of teacher burnout and vigour across the school year and whether teacher emotional intelligence (EI) at the beginning of the school year would predict membership in the trajectories. A sample of 311 school teachers (Mage = 42.40 years ± 9.64 years, aged: 24–61) reported their burnout and vigour at three measurement times during the year and their EI levels at the first measurement time. Analyses revealed two to four trajectories, highlighting the hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 61 publications
1
8
0
1
Order By: Relevance
“…The findings showed that the length of work experience and age were negatively associated with trait EI for the group, as well as for both groups of men and women. The results indicate possible burnout effects that might play a role in lower trait EI scores in older teachers with longer work Lentillon-Kaestner, 2022) suggests that teacher burnout could be prevented by the ability of teachers to manage their own emotions. These reflections ensue from the results not only of theoretical models which presume that emotional intelligence is a skill or type of intelligence, and that it can be modified under the influence of age and experience (Mayer & Salovey, 1997), but also from the results of conducted emotional intelligence training sessions, in which an increase was achieved in the observed respondents (e.g.…”
Section: Discussion a N D Conclusionmentioning
confidence: 88%
“…The findings showed that the length of work experience and age were negatively associated with trait EI for the group, as well as for both groups of men and women. The results indicate possible burnout effects that might play a role in lower trait EI scores in older teachers with longer work Lentillon-Kaestner, 2022) suggests that teacher burnout could be prevented by the ability of teachers to manage their own emotions. These reflections ensue from the results not only of theoretical models which presume that emotional intelligence is a skill or type of intelligence, and that it can be modified under the influence of age and experience (Mayer & Salovey, 1997), but also from the results of conducted emotional intelligence training sessions, in which an increase was achieved in the observed respondents (e.g.…”
Section: Discussion a N D Conclusionmentioning
confidence: 88%
“…The stressful nature of teaching may contribute to low levels of professional wellbeing and a high attrition rate. Teachers in underdeveloped regions are assumed to have more stressors than those who teach in other geographical regions ( Mercer, 2020 ; Cece et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…With regard to certain teachers’ negative engagement that has been identified in the current PDP, it is suggested that PDP organizers should work more closely with local educational authorities and rural schools to provide consistent support in managing the challenges encountered during PDPs ( Gregersen et al, 2020 ; Mercer and Gregersen, 2020 ; Cece et al, 2022 ). For instance, teachers from such remote schools could take turns attending the training program, and the participant teachers’ additional work could be allocated to other colleagues; in return, the teachers who received the training opportunities should share their acquired knowledge through regular teambuilding exercises.…”
Section: Conclusion and Implicationmentioning
confidence: 99%
“…Thus, the concept of vigor refers to a positive and pleasant work effect defined by physical strength, emotional energy, and cognitive alertness (Shirom, 2011). In line with Shirom's approach which considers that the levels of burnout and vigor represent independent factors (Shirom, 2011;Pérez-Fuentes et al, 2019), recent studies have revealed the interest to investigate both teacher burnout and vigor (Cece et al, 2021b). Previous studies have shown evidence for the role of the emotional process on teachers' wellbeing process involving significant relationships between emotions and both burnout and engagement (Jeung et al, 2018;Atmaca et al, 2020).…”
Section: Introductionmentioning
confidence: 99%